Georgi Mamarchev – the hero of the fight for the liberation of Bulgaria in the first half of the 19th century - Rusin, Bartłomiej (Balcanica Posnaniensia. Acta et studia, 2020)
The aim of the article is to show the selected forms of political and military activity of Georgi Stoikov Mamarchev (1786-1846), the iconic Bulgarian national fighter. The main attention is dedicated to G. Mamarchev’s involvement in Russian-Turkish wars (1806-1812; 1828-1829) and the uprising in the Turnovo region in 1835 (the so-called Velchova zavera). Thanks to G. Mamarchev’s activity against Ottoman Empire, during the Bulgarian National Revival period (1762-1878) he was regarded as one the first and most influential Bulgarian freedom fighter. In the following decades he was showed in the context of political activity of his nephew Georgi S. Rakovski (1821–1867).